The Role of Earnings Management Contribution as a Moderation of Social Responsibility Disclosure, Intellectual Capital, and Risk Towards Cost of Capital - Devina Gunawan; Estralita Trisnawati; Sriwati Sriwati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the effect of corporate social responsibility (CSR), intellectual capital (ICD), and risk disclosure (RD) on the cost of capital (WACC), as well as the role of earnings management (TAC) as a moderating variable in financial sector companies listed on the Indonesia Stock Exchange. The research sample was obtained through a purposive sampling method based on the company's annual report. Testing was conducted using moderated regression analysis. The results show that CSR and RD have a significant positive effect on the cost of capital, while ICD has a positive but insignificant effect. Meanwhile, earnings management does not have a direct effect or act as a moderating variable in the relationship between the three types of disclosure and the cost of capital. These findings indicate that investors in the financial sector tend to respond to non-financial disclosures as additional risk signals if they are not supported by transparency and credible governance. Therefore, companies in the financial sector need to convey non-financial disclosures strategically and responsibly to manage market perceptions of risk and capital efficiency.